Militant Islam reaches America 2026-02-15T16:51:18+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Pipes, Daniel, 1949- (W.W. Norton, 2002)

(untitled)
An examination of militant Islam discusses its key features, outlines its differences from traditional Islam, looks at the threat it poses worldwide, and explains what steps must be taken to weaken the movement